Institutional Herding in Bond Markets - Andreas Oehler; George Goeth-Chi Chao (Otto-Friedrich-Universität Bamberg, Lehrstuhl für Betriebswirtschaftslehre, insbesondere Finanzwirtschaft, 2000)
Recent research has shown that institutional herding is a relevant phenomenon in stock markets. Do institutional investors also follow each other in bond markets? This paper focuses on the German bond market and uses data from 57 German mutual funds that invest mainly in DM-denominated bonds, which represents 71% of the total market volume. Due to the variety and large number of bonds that exist, we do not expect mutual funds to herd with regard to separate bonds. We believe instead that bonds with the same characteristics such as interest rate, maturity, collateral, or issuer are considered to be equivalent by institutional investors. Consequently, we construct "bond groups" consisting of similar bonds and analyze herding at a "bond group" level. Our results indicate that there is strong evidence of herding, albeit it is weaker than in stock markets. Further analysis suggests that mutual funds do not place an equal weight on different bond characteristics. Nominal interest rates appear to be most important in the bond selection process.
Keywords: G21; D7; 330; Mutual Funds; Herding; Imitation; Coordination; Behavioral Finance; Rentenmarkt; Institutioneller Anleger; Investmentfonds; Anlageverhalten; Schätzung; Deutschland; herding behavior